(untitled) (Journal of Science and Technology, 2016)
The study reports a case of distance education policy in the Kwame Nkrumah University of Science and Technology (KNUST), a dual mode University in Ghana. The interview method was used to obtain information from 21 purposively selected key informants in the University. Policy documents that addressed Distance Education (DE) were reviewed. The study showed that KNUST has identified DE as a policy initiative for meeting institutional goals. The current DE policy focus was on student support services. However, policy areas under Governance/ Administration and Academic/Faculty/Department were yet to be fully developed. The study recommended a systematic review/audit of existing institutional policies to take care of the needs of distance learners. These needs include addressing key issues of facilities and resources in the Regional centers and documenting policies that showcase the benefits of individual and departmental efforts relating to workload to increase interest, satisfaction and participation in the DE programmes by the various Departments.